PENGARUH SELF EFFICACY TERHADAP MOTIVASI BERWIRAUSAHA PADA MAHASISWA PENDIDIKAN EKONOMI FKIP UNTAN - Gunawan, Angga Arta; Buwono, Sri; Genjik, Bambang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the effect of self efficacy on entrepreneurial motivation on FKIP UNTAN economic education students. The research method used is descriptive with a form of relationship study. Respondents of this study were all students of the economic education FKIP UNTAN class of 2015, 2016 and 2017 Regular / class: A / Morning. The number of population in this study was 191 people, with a total sample of 89 people. The sampling technique in this study uses simple random sampling technique. For data collection using indirect communication techniques (questionnaire), the results showed that there was an effect of self efficacy on entrepreneurial motivation on FKIP UNTAN economic education students which was shown at the significance of Î± 0.05> 0,000. The magnitude of the coefficient of determination in this study amounted to 22.6% while the remaining 77.4% was influenced by the independent variables that not examined in this studyÂ Keywords: Â Self Efficacy, Entrepreneurial MotivationÂ